Economic Constitution of the European Union, before and after Lisbon (between the principle of Competition and the “Social Market Economy”) - Froufe, Pedro Madeira (2017)
This paper registers some notes and interrogations concerning the express legal enshrinement of the concept of Social Market Economy. It highlights the ordoliberal origin of this concept and questions its meaning – associated with a certain loss of intensity from the clear proclamation of the principle of Competition – in terms of the economic ordination of the Internal Market and European integration. However, the question to be asked brings us back to the effective and contextualised characterisation in the current moment of European integration – the economic Constitution of the EU. Will there be, then, a change of the ideological referential in the economic constitution of the EU and, consequently, in the paths that are intended to be trailed in the future? Or, instead, is the emergence of the express enshrinement in the Treaty of the “Social Market Economy” not indicative of a shift of perspective (sense of direction) of the economy in the Internal Market, but only an evolution in continuance?